PELAKSANAAN PEMBEBANAN JAMINAN FIDUSIA PADA PERUM PEGADAIAN CABANG NANGKA KOTA PEKANBARU - , Rika Eva Putri; , Sigid Riyanto, S.H., M.Si ([Yogyakarta] : Universitas Gadjah Mada, 2012)
The aim of this research is to find out the implementation of fiduciary collateral imposition process in Pawnshop Perum Branch Nangka in Pekan Baru city, to discover the execution of Fiduciary Collateral Imposition in Pawnshop Perum Branch Nangka Pekanbaru City. This research use empiric juridical approach that is research that based on the field investigation to support primary data obtained in law sector from the field observation.Based on the result of the research it can be inferred that the imposition process in Pawnshop Perum Branch Nangka in Pekan Baru city, to discover the execution of Fiduciary Collateral Imposition in Pawnshop Perum Branch Nangka in Pekanbaru City that in registering the fiduciary collateral imposition implementation is not appropriate with the valid regulation, such as: principal debt up to Rp 10,000,000 with a letter of authority if the debt trouble it can be made a fiduciary collateral certificate and being registered in fiduciary registering office, principal debt Rp 10,000,000 up to Rp 25,000,000 if necessary the fiduciary collateral certificate registration can be done if there is a trouble debt indication to ease the execution, principal debt over Rp 25,000,000 the fiduciary collateral certificate directly registered and the fiduciary collateral certificate issued by the fiduciary registration office. The execution in fiduciary collateral imposition practice in Pawnshop Perum Branch Nangka in Pekanbaru City concerning large or small credit amount generally by underhanded selling due to the easier implementation process and not require expense so the debtor can return the debt fast and get the returning of debt outstanding debt because if conducting the procedural of execution as the valid regulation then there is a possibility that the debtor do not get the returning by considering the expenses of execution process imposed to the debtor. The requirements of underhanded selling appropriate with the Article 29 the Act of Fiduciary Collateral namely: implemented after a month since informed in the written form by the fiduciary loaner and borrower to the interested parties, if the underhanded selling is not carried out the fiduciary object is drawn by the creditor party or the pawnshop to be executed appropriate with the valid legislation.